Patients admitted to more research‐active hospitals have more confidence in staff and are better informed about their condition and medication: Results from a retrospective cross‐sectional study. Issue 1 (19th February 2019) - Jonker, Leon; Fisher, Stacey Jayne; Dagnan, Dave
Abstract: Rationale, aims and objectives: Clinical research activity in hospitals is associated with reduced mortality and improved overall care quality. In England, the latter is a compound score of several elements and both staff and inpatient feedback form part of the Care Quality Commission (CQC) ratings. The objective of this study was to determine if NHS Trusts' National Institute for Health Research (NIHR) study activity data correlates with specific outcomes from national NHS staff and patient surveys. Method: Retrospective cohort design involving data for 129 English NHS hospital Trusts, including scores from recent national NHS staff and inpatient surveys and NIHR data. Statistical approach involved Spearman correlation analyses, with cut‐off P value ≤ 0.01 for qualification for subsequent principal component analysis (correlation coefficient cut‐off value 0.20). Results: Outcomes of one staff survey question (staff recommendation of the organization as a place to work or receive treatment) and multiple outcomes of inpatient survey questions were positively associated with increased NIHR‐adopted clinical research activity. Better quality of information provision to patients was the dominant theme, though a higher degree of observed staff teamwork, more confidence in the treating doctors, and a better overall inpatient experience also correlated significantly. The number of different studies contributed more to positive associations with survey outcomes compared with the number of recruited participants into research. Conclusions: Survey elements of the CQC appraisal of English NHS Hospital Trusts are significantly associated with increased clinical research activity levels; it appears to drive better information provision to inpatients—particularly around medicine management—and contribute to a better inpatient experience overall, whilst staff are more likely to recommend their own organization. Despite clinical research activity forming a very small fraction of overall NHS activity, it has an indirect positive effect on staff and Trust performance that is measurable at patient level.